Helicene‐type β‐isoindigo‐based boron‐dipyrromethene analogs with strong near‐infrared chiroptical activity - Ziwei Chen; Zhigang Ni; Xing‐Yu Chen; Yongqiang Xu; Chunyan Yu; SiSi Wang; Xiao‐Ye Wang; Hua Lu (Aggregate, 2024)
Abstract Near‐infrared (NIR) chiroptical response has been less explored because it is challenging to achieve both chirality and NIR absorption/emission. Herein, we describe the design of heterohelicene‐type β‐isoindigo‐based boron‐dipyrromethene (BODIPY) analogs (β‐IBs), which shift the absorption peak to 800 nm and produce significant Cotton effects (127.8 M−1 cm−1) and absorbance dissymmetry factors (|gabs| = 3.5 × 10−3). The luminescence dissymmetry factor (glum) and circularly polarized luminescence (CPL) brightness (BCPL) of up to 1.24 × 10−3 and 1.78 M−1 cm−1 were realized beyond 800 nm. These β‐IBs are the first examples of helicene‐type compounds with the highest gabs in the NIR region and CPL beyond 800 nm. Theoretical calculations demonstrate that the strong chiroptical activities are triggered by their large transition magnetic dipole moments. This study not only provides a new approach to the synthesis of a larger variety of unprecedented helicene‐type BODIPY analogs but also demonstrates excellent NIR chiroptical properties.